IDENTIFIKASI PERUMAHAN DAN PERMUKIMAN DI KECAMATAN PALU SELATAN KOTA PALU - Akhmad, Abdul Gani (MEKTEK, 2007)
This study aims at identifying the condition of housing and settlement. This is due to obtaining accurate data which can be used as a guideline in the effor to enhance the quality of the housing and settlement environment. This is a kind of survey on the housing and settlement located in the subdistrict of Palu Selatan, Palu. The data and information on the condition of the housing, facility, and infrastructure with its environment are evaluated and analyzed for conclusions and recommended solution.